In Drosophila melanogaster the COM locus directs the somatic silencing of two retrotransposons through both Piwi-dependent and -independent pathways. - Sophie Desset (Public Library of Science (PLoS), 2008)
Background In the Drosophila germ line, repeat-associated small interfering RNAs (rasiRNAs) ensure genomic stability by silencing endogenous transposable elements. This RNA silencing involves small RNAs of 26-30 nucleotides that are mainly produced from the antisense strand and function through the Piwi protein. Piwi belongs to the subclass of the Argonaute family of RNA interference effector proteins, which are expressed in the germline and in surrounding somatic tissues of the reproductive apparatus. In addition to this germ-line expression, Piwi has also been implicated in diverse functions in somatic cells. Principal findings Here, we show that two LTR retrotransposons from Drosophila melanogaster, ZAM and Idefix, are silenced by an RNA silencing pathway that has characteristics of the rasiRNA pathway and that specifically recognizes and destroys the sense-strand RNAs of the retrotransposons. This silencing depends on Piwi in the follicle cells surrounding the oocyte. Interestingly, this silencing is active in all the somatic tissues examined from embryos to adult flies. In these somatic cells, while the silencing still involves the strict recognition of sense-strand transcripts, it displays the marked difference of being independent of the Piwi protein. Finally, we present evidence that in all the tissues examined, the repression is controlled by the heterochromatic COM locus. Conclusion Our data shed further light on the silencing mechanism that acts to target Drosophila LTR retrotransposons in somatic cells throughout fly development. They demonstrate that different RNA silencing pathways are involved in ovarian versus other somatic tissues, since Piwi is necessary for silencing in the former tissues but is dispensable in the latter. They further demonstrate that these pathways are controlled by the heterochromatic COM locus which ensures the overall protection of Drosophila against the detrimental effects of random retrotransposon mobilization.